Influence of thermal effects on clinch joining of sheet metal - Friedlein, J.; Steinmann, P.; Mergheim, J. (Materials Research Proceedings)
Abstract. Mechanical joining methods, such as clinching, are characterised by locally large plastic deformations of the sheet metal to be joined. The majority of the thereby inserted work is transformed into heat. The heat generation and temperature evolution are systematically studied herein by means of thermomechanical process simulations for joining the dual-phase steel HCT590X and the aluminium alloy EN-AW 6014. The thermal-induced softening of the material is incorporated by a suitable coupled thermoplastic constitutive model. It is observed how the tools significantly and importantly contribute to the heat exchange. They reduce peak temperature increases of 225 K (without heat transfer to tools) to less than 90 K for realistic behaviour of contact heat transfer. Overall, increases in temperature during clinch joining can be expected to remain below 90 K for steel-steel joints and around 50 K for aluminium-aluminium joints.